The community structure of heterotrophic and autotrophic bacteria and microflagellates in four lakes of the Precambrian Shield and the possible roles of bacteria in mercury dynamics in freshwater systems - Samek, Michaela (2007)
This study presents: (1) the ecological significance of bacteria, flagellate and picoplankton in four lakes, (2) development of methodology for the analyses of mercury (Hg) and methylmercury (MeHg) in freshwater particulate fractions, including the bacterial fraction using the AMICON$\sp{\circler}$ dewatering system, (3) determination of the bacterial burden of Hg in one of the lakes examined. Bacteria and flagellates collected during the ice-free season from water columns are described and quantified. The planktonic community was divided into three size fractions based on the longest linear measurements of each particulate fraction. The microbial fraction, measuring 0.1-3 $μ$m, consisted mainly of bacteria and similar size organisms. The bacterial fraction was described and reported in terms of abundance, morphology, and biomass. The fraction measuring 3-20 $μ$m consisted of a mixture of organisms, mainly flagellates, ciliates and algae. The largest fraction, $>$20 $μ$m, consisted principally of zooplankton. A dewatering (AMICON$\sp{\circler}$) system was used to separate and concentrate the microbial fraction from the other fractions. Methods for the analyses of Hg and MeHg were modified to assess these types of samples. The microbial fraction is shown to be the main biotic compartment of Hg. The concentration of Hg in the microbial fraction ranged from 3.7 to 4.6 ng L$\sp{-1}$ using the gas/liquid partition method (GLPM) and 5-8 ng L$\sp{-1}$ by using the gold trap amalgamation method (GTAM) amalgamation method. Samples contained 0.09 to 0.45 ng L$\sp{-1}$ Hg as MeHg. Other fractions and the filtrate contained less than 0.11 ng L$\sp{-1}$ of Hg.